2018
DOI: 10.17987/icfj.v12i0.461
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Anatomical-Functional-RoPE (AF-RoPE) Score Improves Patient Selection for Patent Foramen Ovale Closure

Abstract: IntroductionAlthough recent trials [1] and meta-analysis about transcatheter closure of patent foramen ovale (PFO) [2][3][4][5][6][7] have suggested that PFO closure is both an effective and cost-effective treatment for recurrent embolic stroke, the management of patients with symptomatic PFO is not yet completely clarified. Recently, the RoPE score calculator has been proposed [8] in order to stratify the patients in whom PFO may be considered not a confounding but presumably a causative factor. This score is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Embolic stroke of the undetermined source was def ined as a non-lacunar infarct (subcortical infarct ≤1.5 cm on CT or ≤2.0 cm on MRI) in the absence of the following: extracranial or intracranial atherosclerosis causing >50% luminal stenosis patients at high risk for recurrence who may benefit with PFO closure. 13 Recent studies have shown the importance of identifying high-risk PFOs and the benefits of PFO closure for secondary stroke prevention. 14 These observations are supported by findings of the CLOSE and DEFENSE-PFO trials which included only high-risk PFO patients.…”
mentioning
confidence: 99%
“…Embolic stroke of the undetermined source was def ined as a non-lacunar infarct (subcortical infarct ≤1.5 cm on CT or ≤2.0 cm on MRI) in the absence of the following: extracranial or intracranial atherosclerosis causing >50% luminal stenosis patients at high risk for recurrence who may benefit with PFO closure. 13 Recent studies have shown the importance of identifying high-risk PFOs and the benefits of PFO closure for secondary stroke prevention. 14 These observations are supported by findings of the CLOSE and DEFENSE-PFO trials which included only high-risk PFO patients.…”
mentioning
confidence: 99%